2009
DOI: 10.1128/jvi.00819-09
|View full text |Cite
|
Sign up to set email alerts
|

Turnip Mosaic Virus RNA Replication Complex Vesicles Are Mobile, Align with Microfilaments, and Are Each Derived from a Single Viral Genome

Abstract: Nicotiana benthamiana plants were agroinoculated with an infectious cDNA clone of Turnip mosaic virus (TuMV) that was engineered to express a fluorescent protein (green fluorescent protein [GFP] or mCherry) fused to the viral 6K 2 protein known to induce vesicle formation. Cytoplasmic fluorescent discrete protein structures were observed in infected cells, corresponding to the vesicles containing the viral RNA replication complex. The vesicles were motile and aligned with microfilaments. Intracellular movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
242
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(256 citation statements)
references
References 55 publications
12
242
0
2
Order By: Relevance
“…By contrast, the viral protein 6 kDa protein 2 (6K 2 ) of tobacco etch virus (TEV) and turnip mosaic virus (TuMV) is responsible for initiating the assembly of 6K 2 -induced vesicles (6K 2 -vesicles). These vesicles serve as VRCs, exit ER membranes and eventually assemble into large granule structures at chloroplasts in addition to playing a possible role in cell-to-cell movement (Cheng et al, 2015;Cotton et al, 2009;Jiang et al, 2015;Wei and Wang, 2008;Wei et al, 2010). Out of the three Arabidopsis Sec24 isoforms (Sec24a, Sec24b and Sec24c) (Marti et al, 2010), 6K 2 interacts with Sec24a to assemble 6K 2 -vesicles at ER exit sites (ERES).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the viral protein 6 kDa protein 2 (6K 2 ) of tobacco etch virus (TEV) and turnip mosaic virus (TuMV) is responsible for initiating the assembly of 6K 2 -induced vesicles (6K 2 -vesicles). These vesicles serve as VRCs, exit ER membranes and eventually assemble into large granule structures at chloroplasts in addition to playing a possible role in cell-to-cell movement (Cheng et al, 2015;Cotton et al, 2009;Jiang et al, 2015;Wei and Wang, 2008;Wei et al, 2010). Out of the three Arabidopsis Sec24 isoforms (Sec24a, Sec24b and Sec24c) (Marti et al, 2010), 6K 2 interacts with Sec24a to assemble 6K 2 -vesicles at ER exit sites (ERES).…”
Section: Discussionmentioning
confidence: 99%
“…PCR involved in the gateway cloning was carried out with Phusion DNA polymerase (NEB, Pickering, Ontario, Canada). The recombinant TuMV infectious clone tagged with a chimeric gene containing the 6K-coding sequence fused in frame with the green fluorescent protein (GFP)-coding sequence (TuMV::6K-GFP) was described previously (9,41). The 6K, NIb, and cylindrical inclusion (CI) cistrons of TuMV were amplified from infectious clone TuMV::6K-GFP by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…In seminal work, Carrington and colleagues determined that 6K induces the formation of the ER-derived vesicles for TEV replication (35,38). More recently, viral proteins required for replication and several host factors, namely, eukaryotic initiation factor (isoform) 4E, poly(A)-binding protein, eukaryotic elongation factor 1A, and heat shock cognate 70-3 protein, have been shown to associate with the TuMV 6K-induced vesicles (9,41), raising the possibility that the potyviral 6K vesicles represent sites of viral genome replication. Furthermore, we have demonstrated that the biogenesis of the potyviral 6K vesicles occurs at COPII-accumulating ER exit sites (ERES) on the ER membrane (45).…”
mentioning
confidence: 99%
“…On the other hand, Turnip mosaic virus (TuMV) is a single-stranded Arabidopsis-infecting RNA virus that does have a poly(A) tail in its 3′ UTR. TuMV also contains putative Pumilio-binding core motifs in its genome and 3′ UTR (16). In TuMV-UK1 3′ UTR, putative "UGUA" core sequences were found (Fig.…”
mentioning
confidence: 99%